Glossary of reinsurance terms - Pearce, Eric A. (Assurances, 1973)
We are grateful to the Reinsurance Association of America for permission to reprint the "Glossary of Reinsurance Terms" which the RAA has produced. In its present form, the Glossary is restricted to a relatively small number of terms, but we are confident that having made this start, the RAA will expand this useful publication until it is truly comprehensive. Reinsurance is an important international business and one in which the English language is widely used by great numbers of people to whom English is a foreign language. Many of those who work in the great reinsurance industry must from time to time have felt doubt as to whether a correspondent abroad, or indeed a colleague in the next room, is giving exactly the same weight and meaning to any particular term, as he does himself. Thus it would be of immense benefit to all who are interested in the industry if over the years the expanded Glossary could be accepted internationally and given the force and value usually attributed to a recognized dictionary. If this ideal is ever to become an accomplished fact it is of paramount importance that the Glossary, published for the express purpose of rendering service and avoiding misunderstanding, should as far as possible state its definitions in terms likely to be acceptable not only in the USA but throughout the world. This is, perhaps, of particular interest to Canadian readers who operate in many reinsurance markets, but especially in London and the U.S.A. For this reason, we asked our London correspondent to let us have his observations. These are set out below as footnotes. We should welcome comments from readers, at home and abroad, on the foregoing. Also we should be glad to hear from readers regarding any other reinsurance terms in common use, which it is considered should be included in any future Glossary. These contributions should preferably, but not essentially, give the requisite definition. Assurances.